Iraq's foreign policy towards Iran after the revolution of July 14, 1958-1963 AD: A historical study - Mujbil, Qatran (Al-Adab Journal, 2025)
Foreign and internal political issues of common interest between Iraq and Iran had a clear impact on relations. Political After the revolution of July 14, １９５８ AD, when things had not yet fully stabilized in Iraq, some political contradictions and internal revolutions emerged, which led to the possibility of Iran and its allies influencing its paths and goals in an attempt to form the new regime in IraqThe rapprochement that occurred between the two countries, especially after World War II, helped to overcome many related problems, and after the revolution (July １４, １９５８ AD) in Iraq, Iran began searching for all matters related to the past to raise them against the new government with the aim of weakening it, overthrowing it, or obtaining regional gains. This also happened with regard to the issue of withdrawal from the Baghdad Pact, as well as the issue of the borders in the Shatt al-ArabIraq has made clear that it adheres to friendly relations and cooperation with neighboring Arab countries and adheres to the policy of non-alignment declared by the revolution. As well as emphasizing the issue of borders in the relations between the two countries, as any tension between them on the political level is the first thing that appears in the issue of borders. Especially since the Iranian side used this issue at times when Iraq followed a policy that Iran did not approve of - therefore the issue of the Shatt al-Arab and Iran’s ambitions in it was the gateway to the crisis in the relations between the two countries.Despite this, the Iraqi government tried to avoid confrontation with Iran by trying to reach peaceful solutions to the differences between the two parties.